Pleural Effusion Caused by Bacillus Calmette-Guérin Immunotherapy for Bladder Cancer. (17th June 2017) - Rachakonda, Tara; Kendall, Brian; Spivak, Adam M; Boltax, Jonathan
Abstract: Intravesical bacillus Calmette Guérin (BCG) instillation has been used as immunotherapy for early stage bladder cancer for >40 years. Complications from this therapy are rare but may result in a spectrum of infectious sequelae. Here we describe the case of an elderly man who presented with a pleural effusion and subcutaneous nodule several years after treatment with BCG.